Stability problems lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Bressanone (Bolzano), Italy, June 2-11, 1974 - C.I.M.E. Summer School Bressanone, Italy 1974; Salvadori, Luigi (Heidelberg, Germany Springer Berlin, 2011)
Stabilité asymptotique pour des problèmes de perturbations singulières.- J.K. Hale: Stability of linear systems with delays.- V. Lakshmikantham: Stability and asymptotic behaviour of solutions of differential equations in a Banach space.- P. Negrini: On a definition of total stability for continuous or discrete dynamical systems.-N. Rouche: Théorie de la stabilité dans les équations différentielles ordinaires.- E.O. Roxin: Stability and differ
P. Habets: Stabilité asymptotique pour des problèmes de perturbations singulières -- J.K. Hale: Stability of linear systems with delays -- V. Lakshmikantham: Stability and asymptotic behaviour of solutions of differential equations in a Banach space -- P. Negrini: On a definition of total stability for continuous or discrete dynamical systems.-N. Rouche: Théorie de la stabilité dans les équations différentielles ordinaires -- E.O. Roxin: Stability and differential
Keywords: Differential equations; Stability -- Congresses